SprB Is the Molecular Link between Salmonella Pathogenicity Island 1 (SPI1) and SPI4 - Saini, Supreet (American Society for Microbiology (ASM), 2010)
Salmonella pathogenicity island 1 (SPI1) and SPI4 have previously been shown to be jointly regulated. We report that SPI1 and SPI4 gene expression is linked through a transcriptional activator, SprB, encoded within SPI1 and regulated by HilA. SprB directly activates SPI4 gene expression and weakly represses SPI1 gene expression through HilD.